Copper-zinc-nickel catalyst as well as preparation method and application thereof
By using a copper-zinc-nickel catalyst in methanol liquid phase reforming to produce hydrogen, and using a petal-like ZnO support to disperse Cu-Ni, the problems of poor dispersion of the catalyst and low hydrogen production rate are solved, and high-efficiency hydrogen production and low-cost catalyst preparation are achieved. , suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202411608919.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-27
AI Technical Summary
The existing methanol liquid-phase reforming hydrogen production catalysts have problems such as poor catalyst dispersion and low hydrogen production rate. Traditional precious metal catalysts are costly and prone to inactivation.
The active component Cu-Ni is uniformly dispersed by a ZnO support with a petal-like structure, and prepared by hydrothermal method to control the calcination temperature and time to improve the dispersion and stability of the catalyst.
It achieves the effects of high dispersion, high hydrogen yield rate and high hydrogen selectivity, reduces production costs, and is suitable for large-scale hydrogen production of methanol. The hydrogen production selectivity of the catalyst under 180℃ is higher than 91.82%, and the hydrogen production rate reaches 30.64. μmol·gcat-1·s-1, and maintain more than 82% activity during recycling.
Smart Images

Figure CN119186571A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, in particular to a copper-zinc-nickel catalyst. The invention also relates to a preparation method and application of the catalyst. Background Art
[0002] Compared with traditional fossil energy, hydrogen only produces water as a combustion product, which is a simple, easily available and environmentally friendly secondary energy source. However, due to the flammable and explosive characteristics of hydrogen, the storage and transportation of hydrogen are still great technical challenges. Therefore, how to achieve efficient, safe and economical application of hydrogen energy and develop efficient large-scale storage and transportation technology of hydrogen energy has also attracted widespread attention.
[0003] Circulating hydrogen storage molecules such as methanol have high hydrogen storage density per unit volume and good chemical stability. Methanol is liquid at room temperature, relatively stable and easy to store, making it an ideal liquid hydrogen storage molecule. Traditional methanol reforming hydrogen production is one of the earliest technologies to be studied and applied in industry. It can achieve large-capacity hydrogen production and is one of the important sources of industrial hydrogen. At present, methanol hydrogen production methods can be divided into steam reforming hydrogen production, liquid phase reforming hydrogen production, photocatalytic hydrogen production, etc. The steam reforming hydrogen production device is large, the reaction temperature is high, the energy consumption is high, and the CO concentration in the product is high, which is prone to methanation reaction. At the same time, the hydrogen production rate is low and the hydrogen selectivity is poor. The traditional thermal catalytic methanol liquid phase reforming hydrogen production conditions are mild, and the cost of hydrogen production is lower than that of hydrogen evolution by electrolysis of water. The selection and use of catalysts are key. Most of the catalysts currently used are precious metals (Pd, Pt). Although they have high selectivity, they are too expensive and are not conducive to large-scale production. In addition, too high a temperature for catalytic hydrogen production will lead to catalyst deactivation. Copper-based catalyst is a catalytic material with CuO as the main active component, and also includes ZnO, Al2O3, ZrO2, CeO2 and additive M x O y , additive M x O y The copper-based catalyst is one of MgO, La2O3, CaO or MnO. The copper-based catalyst is applied to the methanol liquid phase reforming hydrogen production reaction. Compared with the conventional copper-zinc-nickel methanol liquid phase reforming hydrogen production catalyst, the CO content in the product is not higher than 1.3 mol%, and the selectivity for CO is low. The Cu-based catalyst has high catalytic activity and selectivity, but the disadvantages are that it is easy to change the crystal phase, the active metal is easy to be leached, the grain size grows and causes deactivation, and the stability decreases in a hydrothermal environment.
[0004] Nickel has high catalytic activity and can effectively promote methanol reforming reaction. The nickel active center on the catalyst surface is conducive to methanol decomposition and hydrogen generation, which can achieve a fast methanol reforming reaction rate, efficiently convert methanol into hydrogen, and generate the required synthesis gas at a high yield. In addition, nickel-based catalysts have good anti-carbon deposition properties, can reduce carbon accumulation under certain working conditions, extend the service life of the catalyst, and maintain high catalytic activity. Compared with other catalysts, nickel-based catalysts have low costs and are suitable for large-scale methanol hydrogen production. It can reduce production costs and improve economic benefits. It has good adaptability under a variety of reaction conditions and can be applied to methanol hydrogen production reactions of different scales to meet the needs of different application scenarios. The prior art discloses a copper-nickel bimetallic catalyst for selective coupling hydrogenation-rearrangement of furfural in aqueous phase to produce cyclopentanone. The technology proposes that the copper-nickel bimetallic catalyst exhibits excellent catalytic ability in hydrogenation rearrangement. The copper-nickel bimetallic combination is used as an active substance in the methanol liquid phase reforming hydrogen production reaction, which can promote the conversion of CO into CO2 through the water-gas shift reaction and increase the hydrogen yield and concentration. Summary of the invention
[0005] In view of the defects and shortcomings of the above-mentioned methanol liquid phase reforming hydrogen production catalyst, such as poor dispersion and low hydrogen production rate, a copper-zinc-nickel catalyst is provided in which the active component Cu-Ni is uniformly dispersed on a ZnO carrier with a petal-shaped structure. The copper-zinc-nickel catalyst has a large specific surface area and can provide more active sites for Cu-Ni, thereby achieving the technical effects of high dispersion, high hydrogen production rate, high stability and high hydrogen selectivity.
[0006] Another object of the present invention is to provide a method for preparing a copper-zinc-nickel catalyst, which has a simple preparation method, low preparation cost and high stability.
[0007] Another object of the present invention is to provide an application of a copper-zinc-nickel catalyst in hydrogen production by liquid phase reforming of methanol.
[0008] To this end, the first technical solution provided by the present invention is as follows:
[0009] A copper-zinc-nickel catalyst, wherein the carrier of the copper-zinc-nickel catalyst is a ZnO carrier loaded with an active component copper-nickel alloy; the active component copper-nickel loading amount is 35% to 65% of the total mass of the catalyst; and the molar ratio of copper to nickel is (8 to 16):1.
[0010] Furthermore, in the copper-zinc-nickel catalyst, the ZnO carrier is a petal-shaped structure with a specific surface area of 100 to 169 m 2 / g; more preferably 169m 2 / g.
[0011] Furthermore, in the above copper-zinc-nickel catalyst, the particle size of the active component Cu-Ni is 5.8-14.7 nm.
[0012] Furthermore, in the above copper-zinc-nickel catalyst, the loading amount of the active components copper and nickel is 55% to 65% of the total mass of the catalyst; and the molar ratio of copper to nickel is 8:1.
[0013] The copper-zinc-nickel catalyst of the present invention uses ZnO with a petal-shaped structure as a carrier, and the flower-shaped ZnO has a petal-shaped morphology of a layer wall, and its porous advantage can further improve the hydrogen production rate. The active component copper-nickel alloy Cu-Ni can be evenly dispersed on the ZnO carrier, and the migration of the active component Cu-Ni is restricted by the morphology of the ZnO carrier, and at the same time, an attachment site is provided for the active component Cu-Ni, further improving the dispersibility of the active component, increasing the reaction contact area of the active component, and preventing the problem of a decrease in the catalytic reaction rate due to the agglomeration of the active component Cu-Ni.
[0014] The second technical solution provided by the present invention is a method for preparing the copper-zinc-nickel catalyst, which comprises the following steps in sequence:
[0015] S1. Mixing zinc acetate, urea and trisodium citrate in a molar ratio of 1:(1-6):0.1 and subjecting the mixture to a hydrothermal reaction, purifying the mixture by an impregnation method and calcining the mixture to obtain a ZnO carrier;
[0016] S2. The copper nitrate, nickel nitrate and ZnO carrier are mixed uniformly, dried and calcined at 250-500° C. for 1-4 h in a nitrogen atmosphere to obtain a copper-zinc-nickel catalyst precursor, wherein the mass ratio of the ZnO carrier, copper nitrate and nickel nitrate is 1:(0.1-1.4):(0.1-1.0);
[0017] S3. Reduce the catalyst precursor in a hydrogen atmosphere to finally obtain a copper-zinc-nickel catalyst.
[0018] Furthermore, in the preparation method of the copper-zinc-nickel catalyst, the molar ratio of zinc acetate, urea and trisodium citrate in step S1 is 1:(1-4):0.1; more preferably 1:2:0.1.
[0019] In step S1, the ratio of zinc acetate, urea and trisodium citrate will affect the morphology and specific surface area of the final ZnO carrier. Therefore, in order to obtain the ZnO carrier with a petal-like structure described in the present invention, it is necessary to reasonably control the ratio of zinc acetate, urea and trisodium citrate.
[0020] In step S1, the addition of urea provides nitrogen to the ZnO carrier, which is then integrated into the active components Cu-Ni, helping to prevent Cu-Ni from aggregating due to migration during the calcination process.
[0021] Furthermore, in the preparation method of the copper-zinc-nickel catalyst, the mass ratio of the ZnO carrier to copper nitrate and nickel nitrate in the step S2 is 1:(0.1-0.5):(0.1-0.3), and more preferably 1:0.5:0.3.
[0022] Furthermore, in the preparation method of the copper-zinc-nickel catalyst, the calcination temperature in step S2 is 400-500° C. and the time is 2-3 h; preferably the calcination temperature is 400° C. and the time is 3 h.
[0023] In step S3, the calcination temperature has a significant effect on the loading amount of Cu-Ni and the coverage of ZnO, so it needs to be precisely controlled. If the calcination temperature is too low, the loading capacity of the ZnO carrier for the active component Cu-Ni will be reduced, thereby reducing the activity of the catalyst. On the contrary, if the calcination temperature is too high, the porous structure of ZnO will be destroyed, which will hinder the active component Cu-Ni from being exposed and agglomerated, thereby affecting the rate of the catalytic reaction.
[0024] The preparation method of the catalyst of the present invention is simple. First, a hierarchical porous ZnO carrier prepared from zinc acetate, urea and trisodium citrate provides active sites. The morphology of ZnO and the catalyst can be controlled by controlling the reaction conditions (calcination temperature, calcination time, etc.), so as to obtain a copper-zinc-nickel catalyst with small particle size, high load and high dispersion. The catalyst can achieve the effects of high hydrogen production rate, strong hydrogen selectivity, strong hydrogen production stability and high catalytic activity. The catalyst can be used for rapid production of high-purity hydrogen and is very suitable for the field of hydrogen production by liquid phase reforming of methanol.
[0025] The last technical solution provided by the present invention is that the copper-zinc-nickel catalyst is used to catalyze the hydrogen production reaction of methanol liquid phase reforming. The prepared copper-zinc-nickel catalyst is added to a reaction solution of methanol and water in a molar ratio of 1:1, and argon is used as a protective gas to carry out a hydrogen production reaction in an intermittent reactor.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. The present invention provides a copper-zinc-nickel catalyst and its preparation method and application, which constrains the migration and agglomeration of the active component Cu-Ni through the petal-shaped structure of the ZnO carrier, effectively prevents Cu-Ni from agglomerating due to sintering, and obtains a high-load and highly dispersed copper-zinc-nickel catalyst. It has the characteristics of strong hydrophilicity, small metal particle size, high catalytic activity and good hydrothermal stability, and can achieve high hydrogen production rate and hydrogen selectivity.
[0028] 2. The copper-zinc-nickel catalyst of the present invention is particularly suitable for catalysis of hydrogen production from methanol liquid phase reforming. It has high hydrogen production rate and hydrogen selectivity. The selectivity of hydrogen in the gas produced at 180°C is higher than 91.82%, and the hydrogen production rate can reach 30.64 μmol·gcat -1 ·s -1 , and the activity can still be maintained above 82% after 10 cycles of in-situ hydrogen production.
[0029] 3. The copper-zinc-nickel catalyst provided by the present invention can adsorb the toxic gas CO produced in the hydrogen production reaction of organic solvent liquid phase reforming, and make it participate in the dehydrogenation reaction of water to generate hydrogen and carbon dioxide, thereby reducing the content of toxic byproduct CO and further improving the hydrogen production rate and hydrogen selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a comparison chart of the performance of methanol liquid phase reforming hydrogen production under the same conditions with different catalysts;
[0031] Figure 2 This is a performance comparison chart of methanol liquid phase reforming hydrogen production for Application Example 1 and Comparative Application Example 4;
[0032] Figure 3 XRD spectra of copper-zinc-nickel catalyst, Cu / ZnO;
[0033] Figure 4 High-resolution transmission electron microscopy (left) and scanning electron microscopy (right) images of copper-zinc-nickel catalyst (Cu-Ni / ZnO);
[0034] Figure 5 Energy dispersive X-ray spectroscopy analysis (left) and scanning electron microscope (right) images of ZnO carriers;
[0035] Figure 6 High-resolution transmission electron microscopy images of the petal-like morphology of the ZnO support (left) and the flake-like morphology of the ZnO support (right). DETAILED DESCRIPTION
[0036] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] Example 1
[0038] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment comprises the following steps:
[0039] S1. Zinc acetate (15 mmol, 3.293 g), urea (30 mmol, 1.802 g) and trisodium citrate (1.5 mmol, 0.468 g) were mixed evenly and kept at 120 ° C for 6 h, centrifuged and washed alternately with deionized water and anhydrous ethanol for 4 times, and calcined in an air atmosphere at 300 ° C for 2 h to obtain a surface area of 169 m 2 / g, ZnO support with petal-like structure;
[0040] S2. Evenly mix copper nitrate (1.6 mmol, 0.096 g), nickel nitrate (0.2 mmol, 0.058 g) and 5 ml of ethanol containing the ZnO carrier (0.2 g) obtained in S1, dry for 12 h, and calcine at 400 °C for 3 h in a nitrogen atmosphere to obtain a copper-zinc-nickel catalyst precursor.
[0041] Among them, the mass ratio of Zn0 carrier, copper nitrate and nickel nitrate is 1:0.5:0.3;
[0042] S3. The prepared copper-zinc-nickel catalyst precursor was reduced in an atmosphere of 350°C at a hydrogen flow rate of 45 ml / min for 2 h to finally obtain a brown copper-zinc-nickel catalyst. The Cu-Ni loading was determined by ICP-OES to be 65.16%.
[0043] The specific surface area is measured by BET method (nitrogen adsorption and desorption).
[0044] Example 2
[0045] The present embodiment provides a method for preparing a copper-zinc-nickel catalyst, wherein the preparation process and parameters are the same as those of Example 1, except that: in S1, zinc acetate (7.5 mmol, 1.647 g), urea (15 mmol, 0.901 g), and trisodium citrate (0.75 mmol, 0.234 g) are contained; the specific surface area of the prepared petal-shaped ZnO carrier is 106 m 2 / g.
[0046] Example 3
[0047] This embodiment provides a method for preparing a copper-zinc-nickel catalyst, and its preparation process and parameters are the same as those in Example 1, except that: S2 contains copper nitrate (0.8 mmol, 0.048 g) and nickel nitrate (0.1 mmol, 0.029 g).
[0048] Example 4
[0049] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment is the same as that in embodiment 1, except that: zinc acetate (15 mmol, 3.293 g), urea (15 mmol, 0.901 g) and trisodium citrate (1.5 mmol, 0.468 g) are used, and the specific surface area of the prepared petal-shaped ZnO carrier is 113 m 2 / g.
[0050] Example 5
[0051] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment is the same as that in Example 1, except that: S2 contains copper nitrate (0.64 mmol, 0.0384 g) and nickel nitrate (0.2 mmol, 0.058 g).
[0052] Example 6
[0053] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment is the same as that in embodiment 1, except that: zinc acetate (15 mmol, 3.293 g), urea (60 mmol, 3.604 g) and trisodium citrate (1.5 mmol, 0.468 g) are used, and the specific surface area of the prepared petal-shaped ZnO carrier is 101 m 2 / g.
[0054] Example 7
[0055] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment is the same as that in Example 1, except that: S2 contains copper nitrate (1.6 mmol, 0.096 g) and nickel nitrate (0.13 mmol, 0.039 g).
[0056] Example 8
[0057] The preparation method of the copper-zinc-nickel catalyst provided in this embodiment is the same as that in embodiment 1, except that the calcination temperature in S2 is 500°C, and the copper-zinc-nickel catalyst is finally obtained. (The specific surface area of the ZnO carrier with a petal-shaped structure is 169 m 2 / g).
[0058] Comparative Example 1
[0059] The preparation method of the copper-zinc-nickel catalyst provided in this comparative example is the same as that in Example 1, except that copper nitrate (0.5 mmol, 1.029 g) and nickel nitrate (0.1 mmol, 0.029 g) are contained in S2.
[0060] Comparative Example 2
[0061] The preparation method of the copper-zinc-nickel catalyst provided in this comparative example is the same as that in Example 1, except that the amount of ZnO carrier used in S2 (0.1 g).
[0062] Comparative Example 3
[0063] Under the same conditions, a catalyst without adding nickel nitrate was synthesized according to the steps shown in Example 1, and 50 mg of the catalyst was weighed and reduced at 350° C. for 2 h at a hydrogen flow rate of 45 ml / min.
[0064] Comparative Example 4
[0065] The purchased copper-zinc-nickel commercial catalyst (CuO / NiO / ZnO) was ground and crushed, and 50 mg of the catalyst was weighed and reduced at 350° C. for 2 h at a hydrogen flow rate of 45 ml / min.
[0066] The specific parameters of the copper-zinc-nickel catalyst Cu-Ni loading amount and the specific surface area of the ZnO carrier provided in Examples 1-8 and Comparative Examples 1 to 4 are shown in Table 1:
[0067] Table 1
[0068] project Cu-Ni loading ZnO support specific surface area Example 1 65.16% <![CDATA[169m 2 / g]]> Example 2 65.16% <![CDATA[106m 2 / g]]> Example 3 31.40% <![CDATA[169m 2 / g]]> Example 4 65.16% <![CDATA[113m 2 / g]]> Example 5 30.22% <![CDATA[169m 2 / g]]> Example 6 65.16% <![CDATA[101m 2 / g]]> Example 7 63.13% <![CDATA[169m 2 / g]]> Example 8 65.16% <![CDATA[169m 2 / g]]> Comparative Example 1 20% <![CDATA[169m 2 / g]]> Comparative Example 2 65.16% <![CDATA[100m 2 / g]]> Comparative Example 3 56.79% <![CDATA[169m 2 / g]]> Comparative Example 4 63.08% <![CDATA[84.9m 2 / g]]>
[0069] Application Example 1
[0070] This application example 1 provides hydrogen production by liquid phase reforming of methanol. 50 mg of the copper-zinc-nickel catalyst prepared in Example 1 is added to 20 ml of a methanol-water reaction solution (the molar ratio of methanol to water is 1:1). 2 MPa argon is used as a protective gas. The hydrogen production performance is tested in an intermittent reactor. After reacting at 180° C. for 45 minutes and then naturally cooling to room temperature, the gas is collected and the gas phase product is quantitatively analyzed by gas chromatography. The results are shown in Table 2.
[0071] The hydrogen production rate of the copper-zinc-nickel catalyst is calculated by the internal standard method using 10% nitrogen / argon inert gas as an internal standard. The hydrogen production rate is the μmol hydrogen content produced per gram of catalyst per second; the selectivity is calculated by the amount of H2, CO, and CH4 in the product, for example, hydrogen selectivity H2 (%) = nH2*100% / (nH2+nCO+nCH4).
[0072] The hydrothermal stability was tested by the following method:
[0073] The CuZnNi catalyst was tested for in-situ recycling at 180°C for 45 min. After cooling to ambient temperature, the gaseous products collected from the autoclave were measured by an Agilent 7820GC with FID and TCD. 2 MPa of 99% Ar was pumped into the sealed autoclave three times to remove gaseous impurities, and then the next experiment was repeated under the same experimental parameters.
[0074] Application Example 2
[0075] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 2. The results are shown in Table 2.
[0076] Application Example 3
[0077] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 3. The results are shown in Table 2.
[0078] Application Example 4
[0079] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 4. The results are shown in Table 2.
[0080] Application Example 5
[0081] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 5. The results are shown in Table 2.
[0082] Application Example 6
[0083] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 6. The results are shown in Table 2.
[0084] Application Example 7
[0085] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 7. The results are shown in Table 2.
[0086] Application Example 8
[0087] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that the catalyst used is the copper-zinc-nickel catalyst prepared in Example 8. The results are shown in Table 2.
[0088] Comparative application example 1
[0089] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1. The difference is that the catalyst uses the copper-zinc-nickel catalyst prepared in Comparative Application Example 1. The results are shown in Table 2.
[0090] Comparative Application Example 2
[0091] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1. The difference is that the catalyst uses the copper-zinc-nickel catalyst prepared in Comparative Application Example 2. The results are shown in Table 2.
[0092] Comparative Application Example 3
[0093] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in application example 1. The difference is that the catalyst uses the copper-zinc-nickel catalyst prepared in comparative application example 3. The results are shown in Table 2.
[0094] Comparative Application Example 4
[0095] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1. The difference is that the catalyst uses the copper-zinc-nickel catalyst prepared in Comparative Application Example 4. The results are shown in Table 2.
[0096] See Table 2 for the catalytic hydrogen production rates and selectivity data of Application Examples 1 to 8 and Comparative Application Examples 1 to 4.
[0097] Table 2
[0098]
[0099] As can be seen from Table 2, the copper-zinc-nickel catalyst provided by the present invention has a high hydrogen production rate and high hydrogen selectivity, and its maximum hydrogen production rate can reach 30.64 μmol·g cat -1 ·s -1 , the hydrogen selectivity can reach 91.82%. From Application Examples 1 and 2, it can be seen that the larger the specific surface area of the ZnO carrier, the higher the hydrogen production rate and hydrogen selectivity.
[0100] Comparative Application Example 5
[0101] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in Application Example 1, except that a 5wt% Pt / C catalyst is used as the catalyst. The results are shown in Table 3.
[0102] Comparative Application Example 6
[0103] The process and parameters of the methanol liquid phase reforming hydrogen production reaction provided in this application example are the same as those in application example 1, except that a 20 wt% Pt / ZnO catalyst is used as the catalyst. The results are shown in Table 3.
[0104] For Application Example 1 and Comparative Application Examples 4-6, please refer to Table 3 for the hydrogen production rate and selectivity under the same conditions.
[0105] Table 3
[0106]
[0107] from Figure 1 As can be seen from Table 3, the selectivity of hydrogen in the gas produced by the copper-zinc-nickel catalyst (Cu-Ni / ZnO) of Application Example 1 at 180°C is higher than 91.82%, the selectivity of carbon monoxide is less than 8.12%, and the selectivity of methane is basically zero, which is better than the 5% platinum / carbon catalyst, the copper-zinc-nickel commercial catalyst of Comparative Application Example 4, and the platinum / alumina catalyst (20% Pt / ZnO), which can greatly reduce the difficulty and cost of subsequent gas purification. The hydrogen production rate of the copper-zinc-nickel catalyst can reach 30.64 μmol·g cat -1 ·s -1 Under the same conditions, it is 3.30 times that of the platinum / zinc oxide catalyst and 36.05 times that of the precious metal 5% platinum / carbon catalyst. However, the copper-zinc-nickel catalyst is more superior in that no methane is produced during the hydrogen production process, and the price of producing the catalyst is much lower, achieving a technological breakthrough in the efficient catalytic hydrogen production by aqueous phase reforming of methanol with non-precious metal catalysts and reducing the cost of catalyst production.
[0108] Figure 2 The test results of the catalysts of Application Example 3 and Application Example 1 are shown. It can be seen that Ni has an effect on improving the hydrogen production performance of the catalyst. The hydrogen production performance of the catalysts synthesized without Ni is compared under the same environment and prepared in the same way. The hydrogen production rate of the Cu / ZnO catalyst is 2.26 μmol·g cat -1 ·s -1 This is because the added Ni is an active component for producing hydrogen, and the porous, petal-like structure of the ZnO carrier can fix more active components Cu-Ni and improve its dispersion. Therefore, the addition of Ni increases the hydrogen production rate of the catalyst by about 2.93 times, and the CO selectivity is also significantly reduced.
[0109] Figure 3 For comparative application example 3 (such as Figure 3 As shown in the figure below) and Application Example 1 (as shown in Figure 3 The XRD spectrum of the catalyst (shown in the upper figure) is Figure 3 Middle and upper picture Figure 3 From the comparison of the middle and lower figures, it can be seen that the signal intensity of the main peaks of zero-valent copper and monovalent copper in the catalyst without Ni is sharper than that of the copper-zinc-nickel catalyst, which means that the Cu particle size of Comparative Application Example 3 is larger, resulting in lower catalyst activity. This is because copper is not easy to agglomerate when it exists in the form of Cu-Ni and can be evenly distributed in the ZnO carrier. However, under the high temperature of calcination, the Cu migration of Comparative Application Example 3 is prone to agglomeration, and the uneven distribution leads to reduced catalytic performance of the catalyst. Under a transmission electron microscope (such as Figure 4left) and under a scanning electron microscope (as shown in Figure 4 The particle size of Cu-Ni in Cu-Ni / ZnO is 7.86nm. The EDS mapping element analysis diagram of ZnO carrier (as shown in the right figure) Figure 5 As shown in the left figure in the middle, it can be seen that Zn is evenly distributed in space, and under a scanning electron microscope (such as Figure 5 As shown in the middle right figure, it can be clearly seen that the ZnO carrier has a petal-like structure. Figure 6 The structure of the sheet (as shown in the left figure) can Figure 6 The ZnO carrier has a large number of active sites, which makes the Cu-Ni highly loaded and dispersed, and has high activity in catalyzing the liquid phase reforming of methanol to produce hydrogen, further improving the hydrogen production performance.
[0110] In order to demonstrate the cyclic performance of the catalyst provided in the present application, the copper-zinc-nickel catalyst prepared in Example 1 was subjected to in-situ cyclic hydrogen production 10 times according to the method provided in Application Example 1, and its activity was measured each time, as shown in Table 4.
[0111] Table 4
[0112]
[0113] It can be seen from Table 4 that the activity can still be maintained above 82%, indicating that the catalyst provided in the present application has good catalytic activity.
[0114] It should be noted that, although other embodiments have been described accordingly for their XRD patterns, transmission electron microscope images and elemental analysis diagrams, their performances are similar. Obviously, these embodiments of the present invention are only used as examples to clearly illustrate the present invention, and are not intended to limit its implementation methods. For those of ordinary skill in the art, other forms of changes or adjustments can be made based on the existing descriptions. It is not necessary and cannot be enumerated here for all possible implementation methods. Any modification, equivalent substitution and improvement made under the scope and principles of the present invention should be deemed to belong to the protection scope of the present invention.
Claims
1. A copper-zinc-nickel catalyst, characterized in that The carrier of the copper-zinc-nickel catalyst is a ZnO carrier, which carries an active component copper-nickel alloy; the loading amount of the active component copper-nickel is 35% to 65% of the total mass of the catalyst; and the molar ratio of copper to nickel is (8 to 16):
1.
2. The copper-zinc-nickel catalyst according to claim 1, characterized in that The ZnO carrier has a petal-like structure and a specific surface area of 100 to 169 m 2 / g.
3. The copper-zinc-nickel catalyst according to claim 1, characterized in that The particle size of the active component Cu-Ni is 5.8-14.7 nm.
4. The copper-zinc-nickel catalyst according to claim 1, characterized in that The loading amount of the active components copper and nickel is 55% to 65% of the total mass of the catalyst; the molar ratio of copper to nickel is 8:
1.
5. The method for preparing the copper-zinc-nickel catalyst according to any one of claims 1 to 4, characterized in that: The steps are as follows: S1. Mixing zinc acetate, urea and trisodium citrate in a molar ratio of 1:(1-6):0.1 and subjecting the mixture to a hydrothermal reaction, purifying the mixture by an impregnation method and calcining the mixture to obtain a ZnO carrier; S2. The copper nitrate, nickel nitrate and ZnO carrier are mixed evenly, dried and calcined at 250-500° C. for 1-4 h in a nitrogen atmosphere to obtain a copper-zinc-nickel catalyst precursor; The mass ratio of the ZnO carrier, copper nitrate and nickel nitrate is 1:(0.1-1.4):(0.1-1.0); S3. Reduce the catalyst precursor in a hydrogen atmosphere to finally obtain a copper-zinc-nickel catalyst.
6. The method for preparing the copper-zinc-nickel catalyst according to claim 5, characterized in that: In the step S1, the molar ratio of zinc acetate, urea and trisodium citrate is 1:(1-4):0.
1.
7. The method for preparing the copper-zinc-nickel catalyst according to claim 5, characterized in that: In the step S2, the mass ratio of the ZnO carrier to copper nitrate and nickel nitrate is 1:(0.1-0.5):(0.1-0.3).
8. The method for preparing the copper-zinc-nickel catalyst according to claim 5, characterized in that: In the step S2, the calcination temperature is 400-500° C. and the calcination time is 2-3 hours.
9. The copper-zinc-nickel catalyst according to claim 1 is used to catalyze the hydrogen production reaction by liquid phase reforming of methanol.
Citation Information
Cited By
Preparation method of copper-nickel alloy electrode and method for preparing wide-proportion synthesis gas by driving CO2 electrocatalytic reduction through copper-nickel alloy electrode
CN121344656A
